Gestión de la calidad y competitividad de la Panadería y Pastelería La Unión de la ciudad de Riobamba período 2021. - Valdez Morocho, María Belén (2022)
Since 2003, “La Unión” bakery and pastry company has been dedicated to making and marketing different kind of bread and cakes in general, offering quality, exquisite taste and excellent service to its customers. Hence, this investigative work about the current situation of the business, located in the city of Riobamba, will be taken into account, which has been working empirically on its quality management, therefore the general objective was to determine how the management of the quality in the competitiveness of the bakery, and as specifics, diagnose the current situation, identify its influence and propose strategies aimed at quality management for the purpose of improving the competitiveness of the business. In the methodology, the hypothetical-deductive method was applied, which investigates inductively, through observation for the formulation of hypotheses, descriptive research was also applied, field investigation for the collection of the necessary information, for this purpose, a survey was designed for the staff, consumers and a semi-structured interview dedicated to the owner. As a sample was taken, 30 people. Subsequently, the results were reflected, which support to create strategies such as a marketing plan, mitigation, training program, machinery innovation, recipe registry, complaints mailbox. Finally, as a conclusion, to continue in the market, its clients must be increased and, in this way, generate more economic income for the benefit of the owner, staff and consumers through strategies regarding quality management to improve the competitiveness of the bakery.